Conjugation of Dasatinib with MHI‐148 Has a Significant Advantageous Effect in Viability Assays for Glioblastoma Cells. (7th August 2019) - Usama, Syed Muhammad; Jiang, Zhengyang; Pflug, Kathryn; Sitcheran, Raquel; Burgess, Kevin
Abstract: We hypothesized that conjugation of the near‐infrared dye MHI‐148 with the anti‐leukemia drug dasatinib might produce a potential theranostic for glioblastoma. In fact, the conjugate was found to bind the kinases Src and Lyn, and to inhibit the viability of a glioblastoma cell line with significantly greater potency than dasatinib alone, MHI‐148 alone, or a mixture of dasatinib and MHI‐148 at the same concentration. It was also used to successfully image a subcutaneous glioblastoma tumor in vivo. Abstract : Theranostic synergy : The heptamethine cyanine dye MHI‐148 was conjugated with dasatinib, and the resulting hybrid compound was found to be highly active against a glioblastoma cell line. Its potency was greater than that of either MHI‐148 or dasatinib alone, as well as the two components administered simultaneously. The dye may help increase dasatinib′s residence time in tumor cells, thereby increasing its efficacy.